2018
DOI: 10.1159/000489198
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Induces Neuronal Apoptosis Through Suppressing Transcription Factor EB Phosphorylation at Ser467

Abstract: Background/Aims: This study determined the role and mechanism of action of transcription factor EB (TFEB) in H2O2-induced neuronal apoptosis. Methods: SH-SY5Y cells were treated with Akt inhibitor/activator and different concentrations of H2O2. Cell apoptosis was detected by flow cytometric analysis. Akt and TFEB phosphorylation and PARP cleavage were determined by Western blotting. HEK293T cells were transfected with different truncated TFEB mutants and HA-Akt-WT; S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 50 publications
(75 reference statements)
0
10
0
Order By: Relevance
“…Reactive oxygen species generated by mitochondrial dysfunction play a significant role in oxidative stress to various types of cells in the brain including microglia, astrocytes, neurons, and endothelial cells, which has been related to inflammation, apoptosis and neurological deficits after SAH (Ayer and Zhang, 2008;Sorce and Krause, 2009;Skowronska and Albrecht, 2013;Sahebkar et al, 2018;Su et al, 2018). The NLRP3 inflammasome composed of NLRP3, ASC and caspase-1, is responsible for the maturation and secretion of proinflammatory cytokines IL-1β and IL-18.…”
Section: Discussionmentioning
confidence: 99%
“…Reactive oxygen species generated by mitochondrial dysfunction play a significant role in oxidative stress to various types of cells in the brain including microglia, astrocytes, neurons, and endothelial cells, which has been related to inflammation, apoptosis and neurological deficits after SAH (Ayer and Zhang, 2008;Sorce and Krause, 2009;Skowronska and Albrecht, 2013;Sahebkar et al, 2018;Su et al, 2018). The NLRP3 inflammasome composed of NLRP3, ASC and caspase-1, is responsible for the maturation and secretion of proinflammatory cytokines IL-1β and IL-18.…”
Section: Discussionmentioning
confidence: 99%
“…Neurons were more vulnerable to ischemia and chemical damage in CSF1-deficient mice [ 58 ]. Following HI, OS was significantly increased which are associated with neuroinflammation, mitochondrial dysfunction, glial/axonal mutagenesis, and synaptic transmission disorders, all contributing to progressive loss of neurons including neuronal apoptosis [ 13 , 59 ]. Our study confirmed that there are increased cellular OS markers MitoSOX and 8-OHdG associated with more FJC-/TUNEL-positive degenerated and apoptotic neurons within the perilesion brain regions of HI rat pups.…”
Section: Discussionmentioning
confidence: 99%
“…These ROS irreversibly oxidize DNA and cellular biomolecules, which creates an additional source of damage in biological systems [37]. Oxidative stress is also more pronounced in neurodegenerative disorders such as Parkinson's disease (PD), where modulation of TFEB has been proposed to reduce neuronal cell death [38,39]. Low concentrations of H 2 O 2 result in the phosphorylation of TFEB by Akt on Ser467, which promotes its nuclear translocation, thus facilitating neuronal survival.…”
Section: Stress As a Pathological Source Of Tfeb Activationmentioning
confidence: 99%
“…Low concentrations of H 2 O 2 result in the phosphorylation of TFEB by Akt on Ser467, which promotes its nuclear translocation, thus facilitating neuronal survival. On the other hand, higher concentrations of H 2 O 2 promote apoptosis in SH-SY5Y TFEB, a new target in CNS disorder cells by suppressing TFEB phosphorylation and nuclear translocation [39].…”
Section: Stress As a Pathological Source Of Tfeb Activationmentioning
confidence: 99%